ANALISIS PENGARUH PERUBAHAN PENGGUNAAN LAHAN TERHADAP DEBIT SUNGAI ( STUDI KASUS SUB-DAS CIKAPUNDUNG GANDOK, BANDUNG ) - Mardi Wibowo (Jurnal Teknologi Lingkungan, 2005)
Now, Bandung area especially Cikapundung Catchment Area is developing rapidly. The development caused the need of area for settlement, business and other constructed area is also increasing. Increase in width of constructed area and decrease in width of forest area cause the run off coefficient is rise and the last, rate of flow the river at rain season is rise and at dry season is decreased. Result of this study are: a) daily minimu rate of flow Cikapundung Gandok Catchment area is decreased with gradient 0,004; b) daily maximum rate of flow Cikapundung Gandok is rise, with gradient 0,1682; c) annually rate of flow Cikapundung river is rise with gradient 0,5685; d) this pattern point a,b,c are caused by using of land that tend convert non-constructed area become constructed area; e) Each type of landuse have same influence on river rate of flow.